Bloom’s Taxonomy in Viewing Sakola Kautamaan Istri’s Educational Conception (A Historical Cultural Study of Sundanese Women Empowerment Concept in 1904) - Restu Dessy Maulida (Universitas Pasundan, 2021)
This research is intended to analyse Sundanese women empowerment concept that put into practice in Sakola Kautamaan Istri (Women Proficiency School) –formerly Sakola Istri- that proposed by Rd. Dewi Sartika in 1904. The school she founded was the first women's fomal and legal educational institution for common civilian class to be established in the Dutch colonialism era when the education for women was considered unnecessary. Bloom’s taxonomy is chosen as the utensil for viewing the educational objective concept and lessons learned at school. The research is included into qualitative descriptive research that employed document analysis approach. The discussion result reveals that cageur, bageur, pinter, wanter (vigorous, kind-hearted, intelligent, courageous) philosophy and the lessons learned at Sakola Kautamaan Istri in 1904 had accomplish the Bloom’s taxonomy domains theory, namely: cognitive, affective, and psychomotor. Keywords: Bloom’s taxonomy, Historical-cultural Study, Sakola Kautamaan Istri, Sundanese Women Empowerment